The Role of Principals in Curriculum Development - Muhammad Almas Perdana Sugianto; Dewi Fikrotul Khoiriyah; Satrio Saifullah; Mohammad Yahya (Universitas Ibn Khaldun, 2026)
This study aims to analyze the role of school principals in curriculum development, particularly in the implementation of the Merdeka Curriculum, which requires flexibility, innovation, and collaboration among school stakeholders. School principals have a strategic function as academic supervisors, managers, administrators, motivators, and transformational leaders who ensure that the curriculum is aligned with the needs of students and the local context. Through a descriptive qualitative approach, this study explores the dynamics of principal leadership in the process of planning, implementing, evaluating, and strengthening teacher capacity in developing learning tools. The results show that consistent academic supervision, effective resource management, and collaboration within the curriculum team can improve the quality of learning and the relevance of teaching materials. However, various challenges such as limited teacher competence, digital infrastructure, and bureaucratic barriers still hinder the optimal implementation of the Merdeka Curriculum. Efforts such as the formation of learning communities, increased professional training, and the integration of Pancasila values have proven to strengthen the effectiveness of curriculum development. Overall, this study confirms that principal leadership is a fundamental factor in realizing adaptive and sustainable curriculum innovation.